Efficiency of Different Trichoderma Isolates on Plant Growth Promoting Activity in Rice (Oryza sativa L.) - Sureshrao, Kale Sonam; Pradeeprao, Kadu Tanvi; Dnyanobarao, Gadambe Shilpa; Agrawal, Toshy; Kotasthane, A. S. (International Journal of Bio-resource and Stress Management, 2023)
The application of Trichoderma strains with biocontrol and plant growth-promoting capacities to plant substrates can help reduce the input of chemical pesticides and fertilizers in agriculture. Some Trichoderma isolates can directly affect plant pathogens, but they also are known to influence the phytohormonal network of their host plant. In the current study, we evaluated the production of potential growth-promoting metabolites (IAA and phosphate) for eight isolates of Trichoderma collected from different geographical locations of Chhattisgarh and some isolates were procured from STRASA-BMGE using 83 elite rice lines. All the eight isolates assessed their growth response onrice. All the Trichoderma isolates were able to release inorganic phosphorus from tri-calcium phosphate and showed consistent ability to produce indole-3-acetic acid (IAA). The production of these metabolites varied greatly within species. Confrontation assays of Trichoderma isolates against two soil borne plant pathogens (Scelrotium rolfsii and Rhizoctonia solani) expressed varying degrees of antagonistic responses, In-vitro antagonism being more effective against R. solani than S. rolfsii. The production of metabolites in all the Trichoderma isolates did not correlate with enhanced root growth in rice lines and bio control efficacy. However, one of the Trichoderma viride isolate (T14) was identified as highest producer of inorganic phosphate, IAA exhibited high antagonistic and plant growth promoting ability. A characteristic aromatic odor resembling coconut in T14 isolate was observed which we speculate is due to 6-Pentylpyrone (one of the best studied secondary metabolites having both antifungal and plant growth-promoting activities. Besides the T14 isolate isolates designated as IRRI-2, IRRI-3 and IRRI-4 were the promising inducer of plant growth.